Advanced Endoscopic Technologies to Improve the Diagnosis of Colorectal Polyps - Daca Alvarez, Maria; Rivero-Sanchez, Liseth; Pellisé, Maria (Digestive Disease Interventions, 2022)
Colonoscopy is the gold standard for colorectal cancer (CRC) prevention. The main quality indicator of colonoscopy is the adenoma detection rate, which is inversely associated with the risk of interval CRC and the risk of death from this neoplasia. In the setting of CRC prevention, diagnostic colonoscopy has undergone a remarkable evolution in the past 20 years. Hand in hand with the implementation of CRC prevention programs and technological advances, we are now able to identify tiny and subtle neoplastic lesions and predict their histology with great efficiency. In this article, we briefly review the endoscopy technologies that can be used to improve the detection and characterization of colorectal polyps.
Keywords: colonoscopy; colorectal cancer; prevention; chromoendoscopy; virtual chromoendoscopy; artificial intelligence; polyps; detection; characterization